Study on the Mechanism of Stabilizing Loess with Lime: Analysis of Mineral and Microstructure Evolution - Yawei Ma; Wenwu Chen (Advances in Civil Engineering)
X-ray diffraction (XRD) technique was adopted to test the mineral composition of quicklime-solidified loess with different lime-adding rates at different curing periods. Scanning electron microscopy (SEM) and nitrogen adsorption were used to analyze the microporous structure of the solidified loess. The unconfined compressive strength and limit moisture content of solidified loess were combined to analyze the evolution mechanism of mineral composition and microstructure of solidified loess with the change of curing period and clarify the mechanism of quicklime-solidified loess. The results showed reduced content of clay minerals and decrease in the number of large pores due to increase of hydrates and pozzolanic products during extended curing period. The solidified soil fabric transformed from a compact structure into a mesh structure composing of acicular crystal and cementation. The main reasons for strength increase and change of liquid and plastic limits with the lime-solidified loess after extended curing are the change of the substance and the microstructure.